Women's empowerment in traditional food value chains at the micro-level: evidence from cassava smallholder farming in Tanzania - Masamha, Blessing; Uzokwe, Veronica N.E.; Thebe, V. (Informa UK Limited, 2018)
Empowering women improves household food productivity and security. We examined women’s empowerment within the cassava value chain according to the five domains of empowerment of the Women’s Empowerment in Agriculture Index, using data from 228 respondents in Tanzania. Disempowerment indices for women and men were 0.95 and 0.14, respectively. Women were disempowered in the production, leadership, and time domains. Women were empowered in the resources domain, which entailed joint ownership and decision making. Marital status and educational levels were significantly associated with women’s empowerment. Policies to improve women’s empowerment should focus on securing ownership of resources and access to credit.